A review and development methodology of a lightweight security model for IoT-based smart devices - Gurunathan M.; Mahmoud M.A. (Science and Information Organization, 2023)
Automation; Cloud data security; Commerce; Intelligent buildings; Network security; Personal computing; Safety engineering; Development methodology; Home smart grids; Lightweight; Lightweight securities; Public clouds; Security mode; Security modeling; Smart devices; Smart homes; Smart objects; Internet of things